Modern Recommendations and Real Clinical Practice: the Results of the SILA Study - O. A. Kislyak; I. I. Chukaeva; V. A. Vygodin (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To assess efficacy and safety of single-pill combination (SPC) amlodipine/perindopril and amlodipine/indapamide/perindopril in patients with uncontrolled hypertension (HT) in routine clinical practice.Material and methods. 16144 patients with uncontrolled HT were included into this multicenter observational study. Eventually 6% of patients were excluded owing to violations of protocol. 15193 patients became subjects to the final statistical analysis; they all were prescribed with single-pill combination amlodipine/perindopril or amlodipine/indapamide/perindopril and subsequently purchased these drugs. Study lasted for 3 months; during this time researchers performed office blood pressure (BP) and heart rate measurements on a monthly basis. Additionally, the researchers registered adverse effects and assessed efficacy and safety using 7-point scale.Results. Initially, patients had an average systolic BP of 1 64.2 ± 1 1.4 mm Hg, diastolic BP - 94.8±8.1 mm Hg, and they also had antihypertensive therapy in 85-89% of cases (in different regions). Patients received ACE inhibitors in 50-54% of cases, angiotensin receptor blockers - in 1 9-23%, calcium channel blockers - in 24-31 %, thiazide diuretics - in 29-36%, beta-blockers - in 27-32%. Monotherapy with ACE inhibitors was used in 1 2-18% of patients, and monotherapy with other antihypertensive drugs - in 1 -4%. Mean age was 60.5 years, mean body mass index - 29.3 kg/m2, 43% of patients had a very high risk by SCORE scale. Prescribed therapy: SPCs amlodipine/perindopril (54%) and amlodipine/indapamide/ perindopril (46%) in different doses. By the end of treatment course, the following results have been got: 88% of patients achieved target BP levels (92% and 85% among patients who took SPCs amlodipine/perindopril and amlodipine/indapamide/perindopril, respectively). Systolic BP decreased by 36,6±11,4 mm Hg (22.0±5.9%), diastolic BP - by 15.6±8.5 mm Hg (16.0±8.1%), pulse BP decreased by 21.0±11.4 mm Hg (28.8±13.9%). Mean efficacy assessment rate was 6.9±0.37 points out of 7; mean safety assessment rate was 6.9±0.37 points out of 7. Adverse events were recorded in 257 patients, which constituted 1.7% of the entire patients' population.Conclusion. Using SPC amlodipine/perindopril and amlodipine/indapamide/perindopril is associated with fast achievement of the target BP levels among most patients with a small number of adverse effects.